Addition of low‐dose liraglutide to insulin therapy is useful for glycaemic control during the peri‐operative period: effect of glucagon‐like peptide‐1 receptor agonist therapy on glycaemic control in patients undergoing cardiac surgery (GLOLIA study). Issue 12 (2nd August 2019) - Makino, H.; Tanaka, A.; Asakura, K.; Koezuka, R.; Tochiya, M.; Ohata, Y.; Tamanaha, T.; Son, C.; Shimabara, Y.; Fujita, T.; Miyamoto, Y.; Kobayashi, J.; et al.
What's new?: During the peri‐operative period in cardiac surgery, adequate glycaemic control is important for the prevention of surgical complications and for improved postoperative prognosis; however, intensive glycaemic control is often associated with hypoglycaemia‐related mortality. The present study showed that the addition of low‐dose liraglutide to insulin therapy achieved greater glycaemic control than insulin alone without serious adverse effects, such as hypoglycaemia. The study suggests that insulin plus a low‐dose glucagon‐like peptide‐1 receptor agonist may be a useful and safe method for achieving peri‐operative glycaemic control and may improve the prognosis in people who have undergone cardiac surgery. Abstract: Aim: To test the hypothesis that the addition of a glucagon‐like peptide‐1 receptor agonist that can decrease glucose levels without increasing the hypoglycaemia risk will achieve appropriate glycaemic control during the peri‐operative period. Methods: We studied 70 people with Type 2 diabetes who underwent elective cardiac surgery. Participants were randomized to either an insulin‐alone or an insulin plus liraglutide 0.6 mg/day group. We evaluated average M values, which indicated the proximity index of the target glucose level from day 1 to day 10. Results: The average M value in the liraglutide plus insulin group was significantly lower than that in the insulin‐alone group (liraglutide plus insulin 5.8 vs insulin‐alone 12.3; P < 0.001). The frequency of insulin dose modification in the liraglutide plus insulin group was significantly lower than that in the insulin‐alone group (odds ratio 0.19, 95% CI 0.08–0.49; P < 0.001). The frequency of hypoglycaemia in the liraglutide plus insulin group tended to be lower than that in the insulin‐alone group (odds ratio 0.57, 95% CI 0.15–2.23; P = 0.21). Conclusions: The results of this study showed that the addition of low‐dose liraglutide to insulin achieved lower M values than insulin alone, suggesting that the addition of low‐dose liraglutide may achieve better glycaemic control during the peri‐operative period. (Clinical trials registry no.: UMIN 000008003)